The global edge : Miami in the twenty-first century - Portes, Alejandro, 1944-; Armony, Ariel C. (University of California Press, 2018)
"Over the last quarter of a century, Miami has transformed into a global city. The Global Edge focuses on the social tensions and unexpected consequences of this remarkable process of change. The rise of a finance and banking center without parallel in the South and the simultaneous emergence of a highly diverse but contentious ethnic mosaic are described and explained. Although Miami is like no other American city, its present condition and future course provides key lessons for other metropolitan areas and for the nation as a whole."--Provided by publisher.
Keywords: Miami (Fla.) -- Social conditions.; Miami (Fla.) -- Economic conditions.; Sociology, Urban -- Florida -- Miami.; Sociologie urbaine -- Floride -- Miami.; POLITICAL SCIENCE -- Public Policy -- Cultural Policy.; SOCIAL SCIENCE -- Anthropology -- Cultural.; SOCIAL SCIENCE -- Popular Culture.; SOCIAL SCIENCE -- Sociology -- Urban.; Economic history; Social conditions; Sociology, Urban; Florida -- Miami